2000
DOI: 10.1080/18811248.2000.9714905
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Rates of Amorphous Silica in Highly Alkaline Solution

Abstract: Cement is an essential materials to construct the subsurface radioactive waste disposal system. However, cementitious materials alter the groundwater pH to highly alkaline condition about 13. To comprehend the effect of such a hyperalkaline condition on the repository surroundings, this study focused on the dissolution rates of amorphous silica at [NaOH]=l0-1 mol·dm-3 . The used samples were three kinds of pure commercial silica and a natural silica scale which was obtained from inside wall of the hot-water pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…According to Figure 3a-c, it is observed that for each temperature, the SiO 2 /Na 2 O mass ratio increases inversely proportional to the concentration of NaOH solution in the aqueous phase. In addition, it is clearly seen that this ratio also increases as a function of the temperature, for the same alkalinity of solution and the same activation time, in accordance with similar studies of the literature [28][29][30][31][32]. Therefore, the higher curing temperatures of the geopolymer pastes as well as the lower NaOH concentrations of the solutions result in higher SiO 2 /Na 2 O mass ratios in the slurries.…”
Section: Characterization Of Geopolymer Pastes Propertiessupporting
confidence: 88%
“…According to Figure 3a-c, it is observed that for each temperature, the SiO 2 /Na 2 O mass ratio increases inversely proportional to the concentration of NaOH solution in the aqueous phase. In addition, it is clearly seen that this ratio also increases as a function of the temperature, for the same alkalinity of solution and the same activation time, in accordance with similar studies of the literature [28][29][30][31][32]. Therefore, the higher curing temperatures of the geopolymer pastes as well as the lower NaOH concentrations of the solutions result in higher SiO 2 /Na 2 O mass ratios in the slurries.…”
Section: Characterization Of Geopolymer Pastes Propertiessupporting
confidence: 88%
“…This database contains detailed thermodynamic properties of minerals forming at low temperatures, including hydrates like C-S-H that form in cements. The dissolution rate constants and the surface area of silica-bearing phases obtained from previous studies [27][28][29][30][31] were loaded in the model to understand and identify the phases responsible for the supply of Si ions to form C-S-H. The silica-bearing phases listed in Table 2 and portlandite were input in the model as reactants.…”
Section: Key Factors That Are Important In the Formation Of C-s-hmentioning
confidence: 99%
“…The dissolution mechanism of amorphous silica is still under discussion. [12][13][14] Considering the disordered structure of amorphous silica, Dove et al 12 proposed a model based on etch pit-driven dissolution, similar to that found for crystalline silica. This involves the creation of vacancy islands on a rumpled Q 3 surface, followed by the retreat of newly created Q 2 step edges.…”
Section: Introductionmentioning
confidence: 94%